1995
DOI: 10.1007/bf00347695
|View full text |Cite
|
Sign up to set email alerts
|

P1 clones from Drosophila melanogaster as markers to study the chromosomal evolution of Muller's A element in two species of the obscura group of Drosophila

Abstract: Thirty P1 clones from the X chromosome (Muller's A element) of Drosophila melanogaster were cross-hybridized in situ to Drosophila subobscura and Drosophila pseudoobscura polytene chromosomes. An additional recombinant phage lambda Dsuby was also used as a marker. Twenty-three (77%) of the P1 clones gave positive hybridization on D. pseudoobscura chromosomes but only 16 (53%) did so with those of D. subobscura. Eight P1 clones gave more than one hybridization signal on D. pseudoobscura and/or D. subobscura chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 16 publications
4
43
0
Order By: Relevance
“…If this inversion was asymmetric, it could have caused more DNA to be translocated to XR from XL than from XR to XL. This is consistent with the in situ hybridization results of Segarra et al (1995), who found that genes move only from element A to D, but not the reverse, and could explain the smaller size of chromosomal arm XL in D. miranda. If each chromosomal arm has on average one crossing over event per meiosis, as suggested on the basis of cytological data in Drosophila (Ashburner 1989), this would imply that genes on chromosome XL undergo twice as much recombination per unit length than genes on other chromosomal arms.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…If this inversion was asymmetric, it could have caused more DNA to be translocated to XR from XL than from XR to XL. This is consistent with the in situ hybridization results of Segarra et al (1995), who found that genes move only from element A to D, but not the reverse, and could explain the smaller size of chromosomal arm XL in D. miranda. If each chromosomal arm has on average one crossing over event per meiosis, as suggested on the basis of cytological data in Drosophila (Ashburner 1989), this would imply that genes on chromosome XL undergo twice as much recombination per unit length than genes on other chromosomal arms.…”
Section: Resultssupporting
confidence: 92%
“…If there is a reasonably good correspondence between size of the polytene chromosomes and sequence physical map, chromosome XL may contain only about half as much DNA as do the other chromosomal arms. In fact, some genes that are located on Muller's element A in D. melanogaster (which corresponds to XL in the pseudoobscura group) map to element D (chromosome XR) in D. pseudoobscura (Segarra et al 1995). Segarra et al (1995) concluded that this is probably the result of a pericentric inversion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overview of the rearrangement process: Figure 3 (Segarra et al 1995). Muller F of D. willistoni has fused to Muller E (Papaceit and Juan 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Muller (1940) overcame this problem when he developed a standard nomenclature that assigned a letter to each of the chromosomal arms or elements on the basis of the Drosophila melanogaster genome (chromosomal arm equals Muller element: X ¼ A, 2L ¼ B, 2R ¼ C, 3L ¼ D, 3R ¼ E, 4 ¼ F). Sturtevant and Novitski (1941) showed that the conservation of chromosomal elements extended to species across the entire genus of Drosophila.The conservation of the gene content within Muller elements across the genus Drosophila has been well supported as more species have been examined and as molecular genetic markers have been used to develop more detailed genetic and physical maps (Spassky and Dobzhansky 1950;Loukas et al 1979;Steinemann et al 1984;Whiting et al 1989;Segarra et al 1995Segarra et al , 1996Ranz et al 1997Ranz et al , 2001Ranz et al , 2003. As the density of genetic and physical markers on the maps of Drosophila species has increased, it has become clear that gene order within Muller elements is not conserved among species (Ranz et al 2001).…”
mentioning
confidence: 99%